Experimental study of thin layer drying behavior of a fish - Erdem, Murat; Varol, Yasin; Öztop, Hakan Fehmi; Kamışlı, Fethi (Springer International Publishing, 2014)
This study covers the drying behavior of rainbow trout (Oncorhynchus mykiss) in a square cross-sectioned dryer. For this, approximately 200 g fish was used to dry at different air inlet velocities like 0.5, 1.5, and 2.5 m/s for the constant air inlet temperature at 46 °C in ranges of 28–43 % of relative humidity. In the experiments, interior temperature values and moisture loses of fish were measured as a function of the drying time. It is seen that the moisture content of the fish has decreased with time and drying procedure for inlet air velocity to be effective. And it is suggested that the fish samples should be dried as single layer at 46 ± 0.1 °C and velocity of 2.5 ms?1 for optimal boundary conductions. © Springer International Publishing Switzerland 2014.
Keywords: Drying; Fish drying; Food drying; Tray dryer